Let f ( x ) be a quintic polynomial such that
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ f ( 1 ) = 2 f ( 2 ) = 2 f ( 3 ) = 3 f ( 4 ) = 4 f ( 5 ) = 6 f ( 6 ) = 9
Determine f ( 7 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = a x 5 + b x 4 + c x 3 + d x 2 + e x + f
So f ( 1 ) = a + b + c + d + e + f = 2
f ( 2 ) = 3 2 a + 1 6 b + 8 c + 4 d + 2 e + f = 2
f ( 3 ) = 2 4 3 a + 8 1 b + 2 7 c + 9 d + 3 e + f = 3
f ( 4 ) = 1 0 2 4 a + 2 5 6 b + 6 4 c + 1 6 d + 4 e + f = 4
f ( 5 ) = 3 1 2 5 a + 6 2 5 b + 1 2 5 c + 2 5 d + 5 e + f = 6
f ( 6 ) = 7 7 7 6 a + 1 2 9 6 b + 2 1 6 c + 3 6 d + 6 e + f = 9
If you solve this system of equations above, you will get that
f ( x ) = 1 2 0 − 3 ∗ x 5 + 5 5 ∗ x 4 − 3 7 5 ∗ x 3 + 1 2 0 5 ∗ x 2 − 1 7 2 2 ∗ x + 1 0 8 0
f ( 7 ) = 9
Problem Loading...
Note Loading...
Set Loading...
Since we are given values of f ( x ) at consecuive points, we can use the Method of Differences here.
x 1 2 3 4 5 6 f ( x ) 2 2 3 4 6 9 D 1 0 1 1 2 3 D 2 1 0 1 1 D 3 − 1 1 0 D 4 2 − 1 D 5 − 3
f ( x ) is a quintic polynomomial, so ( D_5 ) must be constant. Then, we can continue the table and calculate all differences backwards to get f ( 7 ) .
x 1 2 3 4 5 6 7 f ( x ) 2 2 3 4 6 9 9 D 1 0 1 1 2 3 0 D 2 1 0 1 1 − 3 D 3 − 1 1 0 − 4 D 4 2 − 1 − 4 D 5 − 3 − 3